Deformation and instability failure of borehole at high temperature and high pressure in Hot Dry Rock exploitation. (May 2015) - Zhao, Yangsheng; Feng, Zijun; Xi, Baoping; Wan, Zhijun; Yang, Dong; Liang, Weiguo
Abstract: Borehole stability at high temperature and high in-situ stresses is the key to Hot Dry Rock geothermal energy extraction. Upon drilling completion, borehole stability, its deformation and failure critical condition will be significant in deep HDR engineering design and construction. Using high temperature and high pressure servo-controlled triaxial rock testing machine, we performed experiments of borehole deformation and instability for three granite samples (200 mm in diameter and 400 mm long with a 40 mm opening in the center) at different hydrostatic stresses and temperature. The elastic and creep deformation data was analyzed. The results indicate that: 1) when the hydrostatic pressure is lower than 100 MPa and the temperature is below 400 °C, the specimens deform following the generalized Kelvin model. The critical condition for borehole stability is reached at hydrostatic pressure of 125 MPa and temperature of 500 °C, when creep deformation accelerates sharply. The failure mode is shear failure or a combination of shear and tension failure. The critical radial deformation ratio is about 20%; 2) Creep deformation at steady creep phase is derived based on the test data. The ultimate condition for drilling in granite is analyzed in regards to temperature and in-situ stresses. Highlights: Granite deforms following generalized Kelvin model at less than 100 MPa and400 °C. Axial deformation increases linearly with stress and temperature. Borehole radial deformation increases exponentially with stress and temperature. Critical condition for borehole stability is 125 MPa and 500 °C. Formula of ultimate drilling depth is presented involving temperature and stresses.